2011
DOI: 10.1128/iai.01231-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of Salmonella Pathogenicity Island 1 Protein IacP in Salmonella enterica Serovar Typhimurium Pathogenesis

Abstract: Gram-negative bacteria, including Salmonella enterica serovar Typhimurium, exploit type III secretion systems (T3SSs) through which virulence proteins are delivered into the host cytosol to reinforce invasive and replicative niches in their host. Although many secreted effector proteins and membrane-bound structural proteins in the T3SS have been characterized, the functions of many cytoplasmic proteins still remain unknown. In this study, we found that IacP, encoded by Salmonella pathogenicity island 1, was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…IacP could potentially affect the secretion of some SPI1 effector proteins, including SopB, SopA, and SopD (18). To search for other proteins that were differentially secreted in the iacP mutant strain versus the wild-type strain, we investigated the secretion profiles of S. Typhimurium grown under SPI1-inducing conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…IacP could potentially affect the secretion of some SPI1 effector proteins, including SopB, SopA, and SopD (18). To search for other proteins that were differentially secreted in the iacP mutant strain versus the wild-type strain, we investigated the secretion profiles of S. Typhimurium grown under SPI1-inducing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In Escherichia coli, substitution of the conserved serine-36 residue for the 4=-PP binding site of ACP resulted in a biologically inactive protein (27). The observation that replacement with alanine of the serine-38 residue (IacP S38A ), a putative attachment site for the 4=-PP moiety of IacP, did not complement the iacP mutation indicated that that the acylated form of IacP or its ability to carry acyl groups is required for its action during bacterial invasion of host cells (18).In this study, we found that FljB secretion levels were higher in the iacP mutant strain grown under SPI1-inducing conditions and that the expression of FljB was regulated by flagellar phase variation. These results indicate that alterations in lipid metabolism during the bacterial invasion process could trigger the expression of the alternative flagellin monomer FljB.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial cells can internalize and even reproduce within the nonphagocytic epithelial cells (Kim et al, 2011).…”
Section: Discussionmentioning
confidence: 99%